Social media-based civic engagement solutions for dengue prevention in Sri Lanka: results of receptivity assessment - Lwin, May O. (Health Educ Res, 2016)
This article focuses on a novel social media-based system that addresses dengue prevention through an integration of three components: predictive surveillance, civic engagement and health education. The aim was to conduct a potential receptivity assessment of this system among smartphone users in the city of Colombo, the epicenter of the dengue epidemic in the island country of Sri Lanka. Grounded in Protection Motivation Theory (PMT) and using a convenience sampling approach, the cross-sectional survey assessed perceived severity (PSe), perceived susceptibility (PSu), perceived response efficacy (PRE), perceived self-efficacy (PSE) and intention-to-use (IU) among 513 individuals. The overall receptivity to the system was high with a score of >4.00 on a five-point scale. Participants belonging to younger, better educated and higher income groups reported significantly better perceptions of the efficaciousness of the system, were confident in their ability to use the system, and planned to use it in the future. PMT variables contributed significantly to regression models predicting IU. We concluded that a social media-based system for dengue prevention will be positively received among Colombo residents and a targeted, strategic health communication effort to raise dengue-related threat perceptions will be needed to encourage greater adoption and use of the system.